Analysis of Mobile Telephony Development in Croatia - Slavko Šarić; Dragan Peraković; Zvonko Kavran (Promet - Traffic&Transportation, 1970)
Mobile telephony appeared in 1955 and its development inthe world and in Croatia can be divided into two generations:analogue mobile system and digital mobile systems. Mobile te/eplzony is a part of the telecommunication market experiencingthe fastest growth. Already in 1990, the mobile telephonesaccounted for 4% of the world market in telecommunicationservices, and their share is increasing daily. Liberalisation ofthe Croatian market of mobile telephony was a necessity for establishingcompetition as a necessG/y prerequisite for providinghigh-quality se1vices and reducing their prices, and it COJTespondsto the mobile telephony system development worldwide.At the beginning of the 90s, the Republic of Croatia was laggingbehind the telecommunication-developed world, and today shehas a modem infrastructure that supports highly sophisticatedse1vices by two digital and one analogue mobile telephone network.